2022
DOI: 10.1097/md.0000000000032471
|View full text |Cite
|
Sign up to set email alerts
|

The investigation of levels of endothelial cell-specific molecule, progranuline, clusterin, and human epididymis protein 4 in the differential diagnosis of malignant pleural effusions

Abstract: Background: Progranulin (PGRN), endothelial cell-specific molecule-1, clusterin (CLU), and human epididymis protein 4 (HE-4) are novel proteins reported to have diagnostic and prognostic potential in lung cancer. Here, we aimed to identify the markers with high sensitivity and specificity in distinguishing malignant pleural fluids from other pleural fluids. Methods: This prospective, descriptive study was conducted at a medical faculty hospital between 2016 and 2019. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…First, previous studies only included lung cancer patients in MPE. 40,41 Our study found that the mean HE4 in lung cancer (1096 pmol/L) was higher than in other cancers (879 pmol/L). The difference in HE4 was marginally significant (p = 0.06), which may be due to the small sample size of our study.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…First, previous studies only included lung cancer patients in MPE. 40,41 Our study found that the mean HE4 in lung cancer (1096 pmol/L) was higher than in other cancers (879 pmol/L). The difference in HE4 was marginally significant (p = 0.06), which may be due to the small sample size of our study.…”
Section: Discussionmentioning
confidence: 56%
“…HE4 has an AUC of approximately 0.75, lower than that reported in previous studies. [39][40][41] There are several possible explanations. First, previous studies only included lung cancer patients in MPE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In lung cancer, serum HE4 can be used as the diagnosis biomarker for lung cancer (LC), particularly for early-stage LC ( 6 ), and correlates with poor prognosis, especially in Asian patients ( 7 ). HE4 in the pleural fluid can help differentiate malignant effusions from benign effusions ( 8 , 9 ). So far, research associated with HE4 in lung cancer has been mainly focused on serology and pleural effusion, few studies have investigated the clinical significance of HE4 in CSF.…”
Section: Introductionmentioning
confidence: 99%